2020
DOI: 10.1186/s12880-020-00426-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation in patients with clinical suspicion of cerebral venous sinus thrombosis presenting with nontraumatic headache - a retrospective observational study with a validation cohort

Abstract: Background: Clinical suspicion of cerebral venous sinus thrombosis (CVST) is imprecise due to non-specific symptoms such as headache. The aim was to retrospectively assess the diagnostic value of nonenhanced CT (neCT) in patients with nontraumatic headache and clinically suspected CVST. Methods: A retrospective consecutive series of patients referred 2013-2015 for radiology were evaluated. Eligible patients had nontraumatic headache and suspicion of CVST stated in the referral, investigated with CT venography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…However, some sampling bias toward MRI cannot be excluded. Our patients were slightly younger than those previously reported as having undergone CT based on suspected CVST [5]. In addition, the availability of emergency MRI in our institution might lower the threshold to ask for imaging for young, mildly symptomatic patients compared to when only CT is available.…”
Section: Discussionmentioning
confidence: 69%
“…However, some sampling bias toward MRI cannot be excluded. Our patients were slightly younger than those previously reported as having undergone CT based on suspected CVST [5]. In addition, the availability of emergency MRI in our institution might lower the threshold to ask for imaging for young, mildly symptomatic patients compared to when only CT is available.…”
Section: Discussionmentioning
confidence: 69%
“…Statistically, a range of cutoffs have been suggested ranging from 58 HU in a study exclusively on pediatric population 19 and 60 to 70 HU in other age groups. 6 7 8 9 13 15 17 18 20 21 22 23 24 At the start of the last decade, a study looking at eight patients had suggested a cutoff of 70 HU as being 100% specific, as none of normal patients had a sinus attenuation 70 or more. 24 Then a multicentric retrospective study on CVT probability based on visual assessment of spontaneous hyperdensity of cerebral venous system, performed by four blinded radiologists, with 14 positive patients with CVT showed an AUC of 0.992 and density of more than 70 HU only seen in thrombosed segments bar horizontal section of superior sagittal sinus.…”
Section: Discussionmentioning
confidence: 99%
“…The use of magnetic resonance imaging (MRI) sequences (such sequences like T1WI, T2WI, fluid-attenuated inversion recovery (FLAIR), and diffusion-weighted imaging (DWI)) in combination with magnetic resonance venography (MRV) have been largely replaced the use of cerebral angiography and computed tomography (CT), which allows the detection of venous occlusion along with any complications secondary to venous occlusion, such as cerebral edema and areas of venous infarction. 1,9 The use of MRI allows localization of the thrombus within the venous systems by altering the signal intensity in the MRI sequences secondary to disruption in flow due to thrombus. Thrombus in acute stage can lead to a highly subtle abnormal signal intensity on non-contrast MRI, which can be confused with a normal flow void on T2WI.…”
Section: Dates Summaries From Initial and Follow-up Visits Diagnostic Testing (Including Dates) Interventionsmentioning
confidence: 99%
“…The subacute phase takes between 7 to 14 days after that the thrombus become chronic and gives a low to isointense signal in T1WI and high signal in T2WI, which mainly related to vascularization of the connective tissue. 1,9 Here, MRI and MRV are not only helpful diagnostic tools, but also allow to assess the improvement and recanalization of the venous system in follow-up patients.…”
Section: Dates Summaries From Initial and Follow-up Visits Diagnostic Testing (Including Dates) Interventionsmentioning
confidence: 99%
See 1 more Smart Citation